Diversification of rare earth metals supply chain: Can the U.S. rely on non-Chinese sources? - Arsene Oka (Journal of Government and Economics (JGE), 2025)
China's recent restrictions on rare earth (RE) metal exports have heightened U.S. concerns over supply security. A key question is whether non-Chinese producers can substitute for China and reduce dependence. This paper examines that issue by estimating the cross-price elasticity of U.S. RE metal imports from China and the rest of the world (ROW). Positive elasticities imply substitutability, while negative values suggest complementarity, limiting diversification. Using a cointegration-based time-series framework and annual data from 1991-2023, the analysis reveals a clear time horizon distinction. In the long run, Chinese and ROW supplies behave as complements: price increases in one source reduce imports from the other. In the short run, however, they act as substitutes, with higher prices from one source increasing imports from the other. The findings show that while non-Chinese suppliers can provide short-term relief, they cannot fully replace Chinese supply in the long run due to higher costs and limited capacity. China therefore remains structurally indispensable, underscoring the importance of industrial policy and strategic investment in developing a domestic RE metals supply chain. This study provides the first empirical estimates of U.S. RE import demand and disaggregated cross-price elasticities, offering insights for both supply chain managers and government strategists.
Keywords: 330; Rare earth elements (REEs); Import demand elasticity; China-U.S. trade dependence; Supply chain resilience; Cointegrated VAR model; U.S. government REE strategy